2019
DOI: 10.1017/s0950268819001390
|View full text |Cite
|
Sign up to set email alerts
|

Diagnosis of spotted fever groupRickettsiainfections: the Asian perspective

Abstract: Spotted fever group rickettsiae (SFG) are a neglected group of bacteria, belonging to the genus Rickettsia, that represent a large number of new and emerging infectious diseases with a worldwide distribution. The diseases are zoonotic and are transmitted by arthropod vectors, mainly ticks, fleas and mites, to hosts such as wild animals. Domesticated animals and humans are accidental hosts. In Asia, local people in endemic areas as well as travellers to these regions are at high risk of infection. In this revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
68
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 69 publications
(75 citation statements)
references
References 89 publications
2
68
0
5
Order By: Relevance
“…A potential limitation of our study could be cross-reactivity between TG and SFG antibodies (La Scola and Raoult, 1997;Robinson et al, 2019). However, in our study we found that only three participants were seropositive for both TG and SFG, indicating that cross-reactivity between different rickettsial groups with IFA was unlikely.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 60%
“…A potential limitation of our study could be cross-reactivity between TG and SFG antibodies (La Scola and Raoult, 1997;Robinson et al, 2019). However, in our study we found that only three participants were seropositive for both TG and SFG, indicating that cross-reactivity between different rickettsial groups with IFA was unlikely.…”
Section: J O U R N a L P R E -P R O O Fmentioning
confidence: 60%
“…Spotted fever group rickettsiae (SFGR) are emerging infectious diseases with global distribution that are caused by bacteria of the genus Rickettsia. These zoonotic diseases are transmitted by ticks' vectors among wild and domestic animals [21]. Domestic animals and humans are accidental dead end hosts.…”
Section: Discussionmentioning
confidence: 99%
“…These sequences are closely related to R. hoogstraalii, R. asembonensis and R. felis, all of which are members of the spotted fever group rickettsiae (SFG) [28,29,38]. The SFG consists of > 30 species that can be found worldwide, most of them with pathogenic effects on humans [44]. Our analysis showed a close relationship with R. hoogstraalii, a widely distributed bacterium that is still unknown for its pathogenicity in humans.…”
Section: Discussionmentioning
confidence: 66%